Configuração e transformação no campo automotivo: uma análise baseada na distribuição de capitais - Assis, Filippo Savoi de (Universidade Federal de São Carlos, 2023)
The objective of this research was to analyze the configuration and transformation of the automotive sector between the years 2004 and 2018. For the analysis of this sector, the logic of fields was used, which is a socially constructed space, characterized by a set of actors that compete for resources, power and prestige. More specifically, the intention is: to identify the main actors and the relative distribution of capital of companies in the sector; check the structure of the automotive field and indicate the factors that strain competition; understand the influence of financialization in this field. First, capital was collected through indicators for each company. To verify the relationship between these capitals, the Multiple Correspondence Analysis (MCA) was performed, which outlined the structure of the Field in three different periods (2004 to 2008, 2009 to 2013, and 2014 to 2018). It showed the positioning of companies in two dimensions. Dimension 1 (horizontal axis) was strongly influenced by financial, commercial and technological capital and symbolic capital. Dimension 2 (vertical axis) highlights the financialized logic of companies and the focus on developing electric vehicles, elements that are tightening competition in the automotive field. For the period 2004-2013, Toyota has a more developed tendency towards financialization, other companies such as Volkswagen are more resistant to this process. In the years 2014 to 2018, there is a change in this polarization, with the rise of Tesla. Financial capital indicators allowed a study on financialization using statistical tools. Thus, it was verified that the indicators Profit, Revenue and distribution of dividends and Research and Development (R&D) work positively with the market value of companies.
Configuration and transformation in the automotive field: an analysis based on capital distribution
Keywords: Campos; Capitais; Análise de correspondência múltipla; Setor automotivo; Fields; Capitals; Multiple correspondence analysis; Automotive industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS